A Taxonomic Census of Magnoliophytes Associated with forest Abodes of Tribals in Ayodhya Hill Region of Purulia District, West Bengal - Chanda, Soma; Mukherjee, Ambarish (Indian Forester, 2013)
The inventory of the Magnoliophyta (angiosperms) in the forest abodes of the tribes (Paharias, Birhors, Sardars and santhals) in Ayodhya hill shows the community to be composed of 132 species, of which 98 species are dicotyledonous and 16 monocotyledonous. At specific, generic, family and class level, dicots scored high percentages over monocots. The ratios of trees, shrubs, herbs and climbers associated with the forest abodes of tribes of Ayodhya Hill were found to be 44:31:38:19 respectively. Value of Jacard Generic Coefficient of the forest flora was 86.36 which speaks of appreciable taxonomic potential to render stability to the ecosystem. This value is expected in course of time to be progressively reduced to 1. Since the difference between the observed and expected values of generic coefficients is low (13.64), there is a possibility of successful revegetation and restoration of the forests studied.